Hydrocarbon Prospectivity and Petroleum System in West Sumatra Forearc Basin - Perdana Rakhmana Putra; Rusalida Raguwanti (Ikatan Ahli Geologi Indonesia, 2020)
West Sumatra forearc basin lies in the western part of Sumatra island extending from the north to the south. The forearc basin is considered not having potential to produce hydrocarbon due to its low geothermal gradient. However, indications of hydrocarbons were found in Bengkulu A-1X and Arwana-1 wells, which suggest that the Bengkulu forearc basin area has matured source rocks. The Paleogene syn-extensional sediments which are expected to be the main source rock are still under explored, especially those in the outer forearc region. Furthermore, in the Sibolga basin, the Paleogene sediments have not been well explored. Some wells were only drilled up dip of the Paleogene graben and did not penetrate the deeper Paleogene sediments. In addition, Sumatra's forearc region can also have unconventional play potential such as gas hydrate.